Analysis of Primary Metabolic Compounds in Durian Seed Flour (Durio zibethinus Murr) Typical of Central Sulawesi (Parigi Moutong) - Nurhalisa, Nurhalisa; Said, Irwan; Sakung, Jamaluddin M.; Jura, Minarni R. (Jurnal Akademika Kimia, 2023)
This study aims to determine the carbohydrate, protein, and fat content of durian (Durio zibethinus Murr) seeds from Parigi Moutong. This study consisted of two samples, namely, sample A (crushed durian seeds) and sample B (mashed and sifted durian seeds)—Soxhlet method. The results obtained in sample A for carbohydrate content of 52.8 %, protein 3.50 % and fat 2.06 % while in sample B for carbohydrate content of 43.2 %, protein 2.27 % and fat 2.25 %. Based on the results obtained, durian seed flour can be used as processed food and can be of economic value if it is further processed and traded.